EKSPLORASI POTENSI KEPARIWISATAAN DI JAWA TENGAH - - Mabruroh; - Soetarto; - Chuzaimah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2011)
The tourism industry is growing rapidly. According to analyses by the United Nation’s WorldTourism Organization (WTO, 2003), tourism is one of the largest global export industries. During thelatter decades of the twentieth century, tourism developed from a marginal local activity to a globaleconomic giant representing about 6 per cent of the global economy and creating approximately 200million jobs worldwide. In terms of industry size, these statistics mean that the tourism industry is in thesame bracket as agriculture and mining. There are several reasons for this increase in the size of thetourism industry. Personal expenditure on tourism and travelling seems to grow faster than expenditure onother products and services and there is seems to be a greater variety of leisure activities on offer. Thesedevelopments imply that there will be increased competition for people’s time and money. Quality will thusbecome a central issue in customers’ choices of destinations.